2015
DOI: 10.3389/fpls.2015.00862
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hydrogen peroxide in Photosystem II (PSII) using catalytic amperometric biosensor

Abstract: Hydrogen peroxide (H2O2) is known to be generated in Photosystem II (PSII) via enzymatic and non-enzymatic pathways. Detection of H2O2 by different spectroscopic techniques has been explored, however its sensitive detection has always been a challenge in photosynthetic research. During the recent past, fluorescence probes such as Amplex Red (AR) has been used but is known to either lack specificity or limitation with respect to the minimum detection limit of H2O2. We have employed an electrochemical biosensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 74 publications
(105 reference statements)
2
17
0
Order By: Relevance
“…In the spontaneous dismutation, the interaction of two O 2 •– is restricted due to repulsion of the negative charge on the molecule, whereas the interaction of the protonated form of superoxide, hydroperoxyl radical (HO 2 • ), either with O 2 •– or HO 2 • is feasible. Spontaneous dismutation has been recently monitored by real-time detection of H 2 O 2 in PSII membrane under high light using highly sensitive and selective osmium-horseradish modified electrode (Prasad et al, 2015). In the enzymatic dismutation, reduction and oxidation of O 2 •– is associated with the redox change of the redox active metal center which serves as a superoxide oxidase (SOO) and superoxide reductase (SOR), respectively.…”
Section: High Lightmentioning
confidence: 99%
“…In the spontaneous dismutation, the interaction of two O 2 •– is restricted due to repulsion of the negative charge on the molecule, whereas the interaction of the protonated form of superoxide, hydroperoxyl radical (HO 2 • ), either with O 2 •– or HO 2 • is feasible. Spontaneous dismutation has been recently monitored by real-time detection of H 2 O 2 in PSII membrane under high light using highly sensitive and selective osmium-horseradish modified electrode (Prasad et al, 2015). In the enzymatic dismutation, reduction and oxidation of O 2 •– is associated with the redox change of the redox active metal center which serves as a superoxide oxidase (SOO) and superoxide reductase (SOR), respectively.…”
Section: High Lightmentioning
confidence: 99%
“…In photosynthetic organism, generation of reactive oxygen species (ROS) is a quite universal and fast defense mechanism, known to be associated with various stresses both in vivo and in vitro (Yadav and Pospíšil, 2012;Prasad et al, 2015;Prasad et al, 2016;Prasad et al, 2017a;Prasad et al, 2018;Kumar et al, 2019), in both local as well as systemic responses (Grant and Loake, 2000;Slesak et al, 2007). In tomato, it has been observed that hydrogen peroxide (H 2 O 2 ) was produced at the site within an hour of wounding and its level was enhanced even in distant part (upper unwounded leaves) in the following 4 to 6 h (Orozco-Cardenas and Ryan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…From a methodological point of view, the detection of ROS depends mainly on staining and imaging, which would not be easily applied in biohybrids (Steffens et al, 2013 ). Interestingly, constant development of electrochemical methods of H 2 O 2 detection in plant cells should be mentioned (Olvera-González et al, 2013 ; Prasad et al, 2015 ). Probably, they are more applicable in biohybrids, for they omit microscopic image acquisition and processing.…”
Section: Long-distance Signalingmentioning
confidence: 99%